Investigation of functionally graded skew sandwich plates with geometrical deformations under hygro-thermo-mechanical loading - Khanke, Venushree S.; Tande, S.N. (Journal of Structural Engineering, 2024)
This study aims to carry out investigation of functionally graded skew sandwich plates with geometrical deformationsunder hygro-thermo-mechanical loading. It is performed using Higher Order Zigzag Theory (HOZT) and dimensionlessdeflections and stresses are obtained. Using HOZT, the criteria of continuous transverse shear stress at inter-laminarjunctions and zero at the top and bottom surface of the plate is fulfilled. It thus eliminates the requirement of factorfor shear correction. The material properties follow the power law variation and are dependent on temperature andmoisture conditions. The temperature distribution is assumed to be linear and moisture distribution is assumed to beconstant in the study. A 9-noded finite element with 11 dofs at each node is used for discretization of the plate. Theinfluence of governing system components such as aspect ratio (a/h), volume fraction index (n), skew angle, boundaryconditions, geometrical deformation types such as sine, global and local type and deformation amplitudes (ζ0) ondimensionless displacement and stresses is studied. The outcomes from this study are confirmed with those from theprevious studies to authenticate the present formulation. New findings are put forth which can be used as reference forfuture studies in the similar field.